Efficacy of dexmedetomidine versus midazolam when combined with butorphanol for sedation and analgesia during burn dressing changes: A randomized clinical trial - Ding, Xianchao; Cui, Hengfeng; Ma, Peng; Chen, Xi; Sun, Yan; Qu, Minye; Yan, Zhixin (Frontiers in Pharmacology, 2022)
Objective: The aim of this study was to compare dexmedetomidine-butorphanol (DB) and midazolam-butorphanol (MB) combinations for sedation, analgesia in burn patients undergoing dressing changes. Methods: A total of 56 ASA I–II burn patients were included in this prospective, double-blinded study. The ages of these patients were between 20 and 60 years. TBSA ranged from 10% to 50%. They were randomized to group DB and group MB during dressing change. In the DB group, each patient received a bolus dose of dexmedetomidine (0.5μg kg-1) and intermittent boluses of butorphanol (20μg kg-1). In the MB group, each patient received a bolus dose of midazolam (0.05mg kg-1) and intermittent boluses of butorphanol (20μg kg-1). The primary outcomes were sedation scores and pain scores. The second outcomes were vital signs, side effects, and butorphanol consumption. Results: The sedation scores of these two groups did not differ significantly (p>0.05), and the pain scores of these groups were not significantly different (p>0.05). More patients had hypotension in the DB group than in the MB group (6 versus 0, p=0.01), but the number of patients who had respiratory depression was higher in the MB group compared with the DB group (4 versus 0, p=0.038). Butorphanol consumption in the MB group was higher than in the DB group (p =0.025). Conclusion: Dexmedetomidine is comparable to midazolam when combined with butorphanol in burn patients during dressing change. Compared with midazolam, it has the advantage of opioid-sparing effect.